International Power and International Communication - Alleyne, Mark D. author. aut Link
XII, 184 p.
Keywords: Over seven chapters the book shows how international communication has been shaped by the structure of international political power and how these means of global communication have in turn been strategic tools for the exercise of international political power. There are separate chapters on global news flows, the international trade in cultural products (films, books, advertising, recorded music, periodicals and books), and government propaganda activities. The politics of the International Telecommunication Union (ITU), the Universal Postal Union (UPU) and the World Intellectual Property Organisation (WIPO) are analysed.